Trinary Component Adsorption of Methylene Blue, Methyl Orange, and Methyl Red from Aqueous Solution Using TiO2/Activated Carbon - Nguyen Thi Thanh Tu; Tran Si Thanh; Phan Tu Quy; Tran Thi Minh Ha; Phan Thi Kim Thu; Nguyen Hong Bich; Le Van Thanh Sơn; Vo Thang Nguyen; Dao Ngoc Nhiem; Pham Khac Lieu; Dinh Quang Khieu (Adsorption Science & Technology)
Porous TiO2/activated carbon (AC) material was synthesized by grafting peroxo-hydro titanium complexes to rice husk-derived activated carbon. It was found that the morphology of TiO2/AC consists of TiO2 fine particles highly dispersed on the AC matrix. The obtained TiO2/AC composites with high surface area and a red shift exhibit an excellent adsorption performance in both single and trinary system toward methylene blue (MB), methyl orange (MO), and methyl red (MR). The isotherm models including extended Langmuir, P-factor, ideal adsorbed solution theory (IAST) for Langmuir, Freundlich, and Sips models were applied to study the adsorption equilibrium data of trinary solutions. It was found that IAST for Freundlich and Langmuir models were the most suitable one to describe the adsorption of the three dyes on TiO2/AC material. The high maximum adsorption capacities (mmol g-1) in single/trinary mixture were found as 0.452/0.340 for MB; 0.329/0.321 for MO; and 0.806/2.04 for MR. Moreover, the recyclability experiments showed that the adsorbent could be reused through photocatalytic self-cleaning for at least three cycles with stable capacity. Thus, the TiO2/AC can be effectively employed for the removal of dyes from industrial textile wastewater.